Advancing kidney xenotransplantation with anesthesia and surgery - bridging preclinical and clinical frontiers challenges and prospects - Xiaojian Zhang; Hailian Wang; Qin Xie; Yang Zhang; Yixin Yang; Man Yuan; Yuqi Cui; Si-Yuan Song; Jianzhen Lv; Yi Wang (Frontiers in Immunology, 2024)
Xenotransplantation is emerging as a vital solution to the critical shortage of organs available for transplantation, significantly propelled by advancements in genetic engineering and the development of sophisticated immunosuppressive treatments. Specifically, the transplantation of kidneys from genetically engineered pigs into human patients has made significant progress, offering a potential clinical solution to the shortage of human kidney supply. Recent trials involving the transplantation of these modified porcine kidneys into deceased human bodies have underscored the practicality of this approach, advancing the field towards potential clinical applications. However, numerous challenges remain, especially in the domains of identifying suitable donor-recipient matches and formulating effective immunosuppressive protocols crucial for transplant success. Critical to advancing xenotransplantation into clinical settings are the nuanced considerations of anesthesia and surgical practices required for these complex procedures. The precise genetic modification of porcine kidneys marks a significant leap in addressing the biological and immunological hurdles that have traditionally challenged xenotransplantation. Yet, the success of these transplants hinges on the process of meticulously matching these organs with human recipients, which demands thorough understanding of immunological compatibility, the risk of organ rejection, and the prevention of zoonotic disease transmission. In parallel, the development and optimization of immunosuppressive protocols are imperative to mitigate rejection risks while minimizing side effects, necessitating innovative approaches in both pharmacology and clinical practices. Furthermore, the post-operative care of recipients, encompassing vigilant monitoring for signs of organ rejection, infectious disease surveillance, and psychological support, is crucial for ensuring post-transplant life quality. This comprehensive care highlights the importance of a multidisciplinary approach involving transplant surgeons, anesthesiologists, immunologists, infectiologists and psychiatrists. The integration of anesthesia and surgical expertise is particularly vital, ensuring the best possible outcomes of those patients undergoing these novel transplants, through safe procedural practices. As xenotransplantation moving closer to clinical reality, establishing consensus guidelines on various aspects, including donor-recipient selection, immunosuppression, as well as surgical and anesthetic management of these transplants, is essential. Addressing these challenges through rigorous research and collective collaboration will be the key, not only to navigate the ethical, medical, and logistical complexities of introducing kidney xenotransplantation into mainstream clinical practice, but also itself marks a new era in organ transplantation.